Tipos de títeres y la comprensión y expresión oral en los niños de la Institución Educativa Inicial N° 522, Caballococha 2022 - Torres Garcia, Natali Veronica (2023)
This study was carried out with the objective of evidencing how the types of puppets and the oral expression and comprehension of the children of the Initial Educational Institution N° 522 - Caballococha 2022 are related. With a non-experimental design, this study is relational in nature. The population was made up of boys and girls from the Initial Educational Institution No. 522-Caballococha. Survey and observation techniques were used and the observation guide was the instrument used to collect the data after the instruments were previously validated by professional judgment. As a result, the value of the Pearson correlation coefficient was obtained between the variables the types of puppets and the comprehension and oral expression of the children is 0.014 then the correlation between the two variables is low, therefore, there is no significant relationship between the types of puppets and comprehension and oral expression in children of the Initial Educational Institution No. 522- Caballococha 2022